240 Left atrial appendage occlusion: safety, efficacy, and antiplatelet therapy in a single-centre experience. (8th December 2021) - Vignali, Luigi; Barocelli, Federico; Gurgoglione, Filippo Luca; Cattabiani, Maria Alberta; Maini, Arianna; Solinas, Emilia; Benatti, Giorgio; Tadonio, Iacopo; Coli, Stefano; Pelà, Giovanna Maria; Niccoli, Giampaolo
Abstract: Aims: Oral anticoagulation (OAC) is the cornerstone therapy for stroke prevention in patients with atrial fibrillation (AF). However, a not negligible proportion of AF patients experiences major bleeding events or is affected by concomitant disorders that represent a contraindication for OAC. Left atrial appendage occlusion (LAAO) has emerged as an effective strategy to minimize the risk of thromboembolism in AF patients (without moderate/severe mitral stenosis or mechanical prosthetic heart valves) that are poor candidates for OAC. After the procedure variable regimens of antithrombotic therapy are prescribed, in order to provide protection and prevent device-related thrombus (DRT). The optimal post-procedural antithrombotic strategy remains to be assessed. Therefore, we aim to evaluate the safety and efficacy of LAAO procedure and the relationship between antiplatelet therapy and outcomes at long-term follow-up. Methods and results: We conducted a retrospective observational study including consecutive AF patients who underwent LAAO at Azienda Ospedaliero-Universitaria of Parma from October 2010 to June 2021. The incidence of major ischaemic events [DRT, ischaemic stroke, transient ischaemic attack (TIA) and systemic embolism], Bleeding Academic Research Consortium major bleeding events and net adverse clinical events (major ischaemic + bleeding events) were assessed at follow-up. We enrolled 130 patients [median age 77 years (73; 81)] characterized by both high ischaemic (mean CHA2DS2-VASc 4.48) and bleeding risk (mean HAS-BLED 3.24). Technical procedure success was achieved in 123 (94.6%). Thirty-nine (31.7%) patients were discharged on short (≤1 month)-dual antiplatelet therapy (DAPT); 35 (28.5%) on long-DAPT (1–12 months) and 49 (39.8%) on single antiplatelet therapy (SAPT). Antiplatelet therapy was chosen after multidisciplinary discussion on the basis on the hemorrhagic risk [mean HAS-BLED 3.55; 3.11; 2.97 ( P  = 0.038) in SAPT, short-DAPT and long-DAPT groups respectively], while no differences were observed in ischaemic risk between the three groups. Clinical follow-up was completed in 119 (98.2%) of successfully implanted patients. After a median follow-up of 31 ± 16 months, 24 (20.2%) patients had a major adverse event: 11 (9.2%) ischaemic events [8 (6.7%) strokes and 3 (2.5%) TIA] and 13 (10.9%) major bleedings. Patients on short-DAPT had a significantly lower occurrence of major bleedings [0 vs. 4 (11.4%) on long-DAPT vs. 9 (18.4%) on SAPT; P  = 0.033] and net adverse clinical events [3 (7.7%) vs. 7 (20.0%) on long-DAPT vs. 14 (28.6%) on SAPT; P  = 0.005] compared to the other two groups, while no difference was observed in the incidence of major ischaemic events [3 (7.7%) on short-DAPT vs. 3 (8.6%) on long-DAPT vs. 5 (10.2%) on SAPT; P  = 0.340]. Conclusions: In our cohort of AF patients with a contraindication for OAC therapy, LAAO showed high procedural success; however, long-term major ischaemic and bleeding events were not negligible. Short-DAPT therapy turned out to be the best antiplatelet regimen regarding net ischaemic-hemorrhagic balance. Evidence from well-designed randomized trials would be desirable to guide a tailored approach in the selection of post-procedural antithrombotic regimens.